16S rRNA Gene Analysis of Chlorate Reducing Thermophilic Bacteria from Local Hot Spring - Aminin, Agustina L. N.; Katulistiwasari, Puri; Mulyani, Nies Suci (JURNAL SAINS DAN MATEMATIKA, 2011)
Chlorates waste remediation by biological processes has been the object of current research. Strain CR, the chlorate reducing bacteria was isolated from Gedongsongo hot spring using minimal medium broth containing chlorates and acetate at 55oC. The determination of chlorate reduction from medium was carried out using turbidimetric method. CR isolate showed reducing ability 18% after four days of incubation. The phenotypic character of CR isolate including rod-shaped cells, gram-positive bacteria and facultative anaerobes. On the basis of 16S rRNA analysis, CR isolate was closely related to Bacillus pallidus, Aeribacillus E3, Geobacillus pallidus and Geobacillus sp.D64. The similarity of nucleotide sequences of 16S rRNA gene was 97%, suggested as a novel species. Â Keyword: thermophilic bacteria, chlorate reducing, 16S rRNA gene